THE CREATION OF MAQSUD SHAYKHZODA-AS A GOLDEN LEGACY ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
this article spoke about the importance of the work of Maqsud Shaykhzoda in the education of young people, such qualities as courage, fairness, thoughtful thinking, popularism, expressed in the image of the heroes of the work in Uzbek literature.